Suicide in Elderly Patients with Hip Fracture: A South Korean Nationwide Cohort Study. (17th June 2020) - Jang, Suk-Yong; Yang, Dae-Suk; Cha, Yong-Han; Yoo, Heon-Jong; Kim, Kap-Jung; Choy, Won-Sik
Abstract : Background: The purpose of the present study was to evaluate the incidence rate (IR) of suicide in elderly patients with hip fracture on the basis of a nationwide cohort and to analyze the change in the hazard ratio for suicide after hip fracture over time in comparison with a control group. Methods: Patients with hip fracture and their matched controls were selected from the National Health Insurance Service-Senior cohort (NHIS-Senior) of the Republic of Korea. The NHIS-Senior consists of 558, 147 people selected by a 10% simple random-sampling method from a total of 5.5 million subjects ≥60 years of age in 2002. Risk-set matching (1:2) on the propensity score was performed with use of a nearest neighbor matching algorithm with a maximum caliper of 0.1 for the hazard components. The IR of suicide and 95% confidence interval (CI) were calculated on the basis of a generalized linear model with a Poisson distribution. The effect size was presented as a hazard ratio (HR) with use of the Cox proportional-hazard model with a robust variance estimator that accounts for clustering within matched pairs. Results: A total of 11, 477 patients with hip fracture and 22, 954 matched controls were included. The mean duration of follow-up was 4.59 years, generating 158, 139 person-years. During follow-up, a total of 170 suicides were identified. Comparisons at up to 180 days and 365 days showed that patients with hip fracture were at higher risk for suicide than matched controls (p = 0.009 and 0.004, respectively; stratified log-rank test). During the first 180 days of follow-up, 14 suicides were identified in patients with hip fracture during 11, 152 person-years (IR, 266.1 per 100, 000 person-years; 95% CI, 157.6 to 449.4). Patients with hip fracture were 2.97 times more likely to kill themselves than their matched controls during the same period (HR = 2.97; 95% CI, 1.32 to 6.69). Conclusions: Hip fracture in elderly patients increased suicide risk within a year. A new approach to psychiatric evaluation and management is needed in elderly patients with hip fracture. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.